2009
DOI: 10.3324/haematol.2009.013243
|View full text |Cite
|
Sign up to set email alerts
|

Additional chromosome abnormalities in patients with acute promyelocytic leukemia treated with all-trans retinoic acid and chemotherapy

Abstract: BackgroundAcute promyelocytic leukemia is a subtype of acute myeloid leukemia characterized by the t(15;17). The incidence and prognostic significance of additional chromosomal abnormalities in acute promyelocytic leukemia is still a controversial matter. Design and MethodsBased on cytogenetic data available for 495 patients with acute promyelocytic leukemia enrolled in two consecutive PETHEMA trials (LPA96 and LPA99), we analyzed the incidence, characteristics, and outcome of patients with acute promyelocytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 22 publications
8
64
6
Order By: Relevance
“…It remains speculative whether this aspect could contribute to explain the weaker prognostic impact of the FLT3-ITD in Impact of FLT3-ITD mutation load in acute promyelocytic leukemia haematologica | 2011; 96(12) The frequency of ACA in our cohort (38.8%) was similar to that in previous studies. [32][33] In general we did not find that ACA had a significant impact on prognosis, which is in accordance with our previous study in 50 patients with APL. 34 Cervera et al from the PETHEMA study group found that ACA were associated with higher rates of coagulopathy, lower platelet counts, and higher relapse risk scores in APL, but remission rates of patients with and without ACA were nearly the same, being 90% and 91%, respectively.…”
Section: Flt3-tkd (N=18)supporting
confidence: 82%
See 1 more Smart Citation
“…It remains speculative whether this aspect could contribute to explain the weaker prognostic impact of the FLT3-ITD in Impact of FLT3-ITD mutation load in acute promyelocytic leukemia haematologica | 2011; 96(12) The frequency of ACA in our cohort (38.8%) was similar to that in previous studies. [32][33] In general we did not find that ACA had a significant impact on prognosis, which is in accordance with our previous study in 50 patients with APL. 34 Cervera et al from the PETHEMA study group found that ACA were associated with higher rates of coagulopathy, lower platelet counts, and higher relapse risk scores in APL, but remission rates of patients with and without ACA were nearly the same, being 90% and 91%, respectively.…”
Section: Flt3-tkd (N=18)supporting
confidence: 82%
“…In their study, no specific ACA was an independent risk factor for relapse. 33 The European APL group also did not find that ACA had a significant impact on prognosis, 32 and Slack et al found no difference in overall survival between APL patients with an isolated t(15;17)/PML-RARA and patients with ACA. 26 Accordingly, we were not able to show a significant influence of ACA on outcome in patients with APL.…”
Section: Flt3-tkd (N=18)mentioning
confidence: 99%
“…Other abnormalities involve number 7, 9, and 16 chromosomes; 14,15 however, the association of t(9;11)(q13;p13), which was observed in the present patient, has not been reported, and thus appears to be novel. Furthermore, t(9;11) itself with the breakpoints of (q13;p13) has not been reported in hematologic malignancies.…”
Section: Discussioncontrasting
confidence: 39%
“…It has been reported that APL patients showing additional chromosomal abnormality are associated with more marked coagulopathy and a poor prognosis. 15 However, several clinical trials reported that there were no significant differences in the complete remission and overall survival rates between APL patients with solely t(15;17) and additional abnormalities. 17,18 The mechanisms of the persistent hypoplasia in APL are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that trisomy 8 and 21 and abn (17) are the three most frequently observed aberrations, in addition to t(15;17), in APL (22)(23)(24)(25). To date, there has only been one case report describing 3q29 involved in translocation changes, rather than additional changes (26).…”
Section: Discussionmentioning
confidence: 96%